Tragic Hesitation In William Shakespeare's Hamlet:A Psychoanalytic Perspective - Fahas, Rida (2012)
The major problem of this study is how the tragic hesitation is reflected in the major character's personality. The aims of this study is to analyze William Shakespeare's Hamlet drama based on the structural elements and the development of personality of the major character based on Psychoanalytic Perspective. This study focuses on the major character, namely Hamlet. The method of data collection is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the script of the play itself, while the secondary data source includes books and other data that have relationship with the research. Technique of the Data Collection is taking note, while the technique of Data Analysis in this study is descriptive analysis. Based on the structural analysis, it is evident that in this drama, William Shakespeare wants to deliver a message that hesitation can bring a loss to us and other people. Based on the psychological analysis, it is clear that in Hamlet drama Shakespeare describes a psychological phenomenon, in which the major character, namely Hamlet always hesitates in dealing with problems.